Prognostic value of renal function in patients with acute decompensation of chronic heart failure - I. A. Meray; A. Yu. Yurovsky; E. P. Pavlikova; M. A. Efremovtseva; V. S. Moiseev (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study renal function and prognostic value of creatinine and glomerular filtration rate (GFR) levels in regard to lethality among patients with acute decompensation of chronic heart failure (AD CHF).Material and methods. Fhe study included 392 patients hospitalized with AD CHF symptoms (mean age 65,2+8,4 years; 263 (68%) males; CHF duration - 3,6 years). Serum creatinine concentration was measured daily up to Day 7 of hospitalization. Persistently elevated creatinine level by at least 26,5 mkmol/1 pointed to deteriorating renal function. GFR was calculated according to Cockroft-Gault formula. Echocardiography at admission was performed in all participants.Results. Baseline renal dysfunction (GFR<90 ml/min/1,73 m2) was observed in 270 (69%) patients, hospitalized with AD CHF. Severe renal failure (RF) - GFR<30 ml/min/1,73 m2, was observed in 54 (20%) subjects, including 11 (4%) with terminal RF - GFR<15 ml/min/1,73 m2. Deterioration of renal function during hospitalization was registered in 120 (30,6%) patients, being linked mostly to CHF duration. In this group, 13 (10,8%) patients died - substantially more than in participants without progressing renal dysfunction (19 (7%) deaths).Conclusion. In patients hospitalized with AD CHF, baseline GFR decrease was observed in 69%, including 20% with severe renal dysfunction (GFR<30 ml/min/1,73 m2). Renal dysfunction progression during hospitalization, registered in 30,6% of AD CHF patients, was linked to CHF duration and higher lethality.